Analisis Pengaruh Penambahan Pupuk Air Nira Terhadap Pertumbuhan Rumput Laut Caulerpa racemose dengan Kedalaman yang Berbeda - Baiq Nopi Kartika; Moh. Awaluddin Adam; Dewi Putri Lestari (Faculty of Science and Technology University Ibrahimy, 2023)
One effort to increase the growth of Caulerpa racemosa and support production without depending on the season is by fertilizing. This research aims to analyze the use of nira water fertilizer in the cultivation of Caulerpa racemosa seaweed at different depths. The research was carried out at the National Innovation Research Agency (BRIN) Malaka, Pemenang, North Lombok Regency, West Nusa Tenggara and took place from October to December 2022. The research materials used consisted of sea water, nira water, Vitamin B1, and Caulerpa racemose. The equipment used in this research included: stationery, concrete tubs, stones, scissors, cell phones, plastic baskets, rulers, NO2 Profi Test, NO3 Profi Test, pH meter, ris rope, analytical scales, waring, and water quality checker. This research was carried out by preparing containers, preparing containers for seeds, caring for seeds, applying nira water fertilizer, observing growth, observing water quality. The research parameters are: weight measurement, length measurement, survival and specific growth rate. The results of the NPK level test in the nira water used in this research were N total: 0.13 ppm, P Total: 0.002, and N Total: 0.002. The results obtained were the average length of new shoots = 3.74-4.01 cm; average weight = 88.33 gr – 92.22 gr; specific growth rate = -1.89 % - (-3.04 %); survival value = 65.67%-78%. Data analysis using the One Way Anova Test of the three treatments had no significant effect (p<0.05). Nira water fertilizer as liquid organic fertilizer in caulerpa recemosa cultivation can support the weight and length growth of caulerpa racemosa. However, it has not been able to increase survival and specific growth rate in caulerpa racemosa.